Study of Ettawa Crossbreed’s Grade for Source at Livestock Farmer in East Lombok Regency (Case Study on Livestock Farmers) - Muhammad Dohi; Kertanegara; I Nyoman Sadia; A Rai Somaning Asih; Hermansyah Pany (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
This study to determine the performance of shoulder height, body weight and grade of PE goats kept by livestock farmers in East Lombok Regency. This research was conducted from June to July 2022 using survey methods, observations and direct interviews with livestock farmers in East Lombok Regency. the location where the research was carried out based on recommendations from the Puskeswan. Pringgabaya, Sakra Barat and Jerowaru sub-districts are the 3 sub-districts that are the research locations, from each selected sub-district there are 3 villages representing each sub-district and 10 livestock farmers in each village, with details of 3 sub-districts, 9 villages and 90 livestock farmers. The variables observed in this study included the identity of the livestock farmer, the rearing system, the housing system, performance (body weight and shoulder height) and the farmer's grade of PE goat. Data were analyzed using Arithmetic Mean and Standard Deviation. Most of the high shoulder performance of PE goats in East Lombok Regency is not standardized by SNI 7352;2015. The grade of PE goats in East Lombok Regency were 58 PE goats aged 4-8 months which entered grade D and 9 goats entered grade C, 75 PE goats aged 8-12 months which entered grade D and some livestock in Jerowaru District is included in E while 13 goats in West Sakra District are included in grade C, 165 PE goats aged 12-36 months are included in grade D and 9 goats are included in grade C, 58 PE goats aged 4-8 months are included into grade D and 9 goats entered into grade C, 38 PE goats aged 36 months and over entered into grade C.